Feasibility of the Participatory Experience Survey and the Setting Affordances Survey for use in evaluation of programmes serving youth with intellectual and developmental disabilities. (15th September 2016) - Liljenquist, K.; Coster, W.; Kramer, J.; Rossetti, Z.
Abstract: Background: Participation by youth with disabilities in recreational activities has been shown to promote the development of important skills needed for transition to adulthood. The Participatory Experience Survey (PES) and the Setting Affordances Survey (SAS) were developed for use by recreational programmes serving youth with significant intellectual and developmental disabilities (SIDD) to assess participant experiences and ensure that participants are afforded optimal opportunities to develop these skills. This paper presents a feasibility evaluation to determine the appropriateness of the PES and the SAS for use in a programme evaluation context. Method: The PES and the SAS were used to evaluate a programme serving youth with SIDD in the greater northwest region of the United States. Three recreational activities were evaluated: an art project, trip to a zoo and a track practice. Programme volunteers used the SAS to assess opportunities and affordances offered within each activity. The PES was then given to 10 young people in each activity to capture their experiences. It was hypothesized that each setting would afford different experiences and developmental opportunities because of the differing nature of the activities. Results: The PES and SAS were found to be feasible for conducting a programme evaluation. All three settings offered varying types of experiences and affordances. Notably, as measured by the SAS, opportunity for skill development was greater in more structured activities; the zoo had the fewest opportunities for skill development and the art project had the most skill development opportunities. Youth answered 'no' most often to 'asking for help' and 'helping a kid', suggesting changes to offer more opportunities to develop these skills would be beneficial in all three activities. Conclusion: These new instruments offer programmes a means to more fully include young people with disabilities during programme evaluations, leading to better‐structured, more supportive programmes.